The Level of SGOT and SGPT after The Administration of Powdered Colorant Pigment Isolated from Kesumba Keling’s (Bixa Orellana) Seed Coats An experimental study in Balb/C Mice - Suparmi, Suparmi; Isradji, Israhnanto; Fatmawati, Dina (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: There has been an effort to explore pigment from kesumba keling’s (Bixa orellana) seed coats for a source of natural food colorant. Consumption of pigment from kesumba keling (Bixa orellana) was assumed to cause adverse effects on heart as an important organ in detoxification or inactivation of drugs or other toxic compounds. This study conducted to determine the levels of SGOT and SGPT blood serum of mice (Mus musculus) Balb/C after administration of colorant powder pigment of B. orellana seed coat’s at various concentrations.Design and Methods: The research is an experimental research with Factorial Design with 2 factors. Food Colorant Powder was made from bixin, norbixin, and crude extract pigment isolated from B. orellana seed coat’s. A total of 60 male mice were divided into 10 treatment groups. Powdered colorant solution at the concentration of 0% (control), 1%, 5%, and 10% were orally administered using gavage as much as 1 ml a day for 30 days.Results: Kruskal Wallis test results shows a not significant difference SGOT and SGPT level among the groups (p > 0.05), thus consumption of colorant powder of bixin, norbixin, and the crude extract with various concentrations did not affect the SGOT and SGPT.Conclusion: Colorant powder isolated from B. orellana seed coat’s has been shown to have no effect on the liver function, so it is safe as food colorant (Sains Medika, 3(1):69-77).